Selective Hydrogenation of Benzene to Cyclohexene over 2Ru/La2O3‐ZnO Catalyst without Additional Modifiers. Issue 16 (28th July 2016) - Spod, Hendrik; Lucas, Martin; Claus, Peter
Abstract: Selective benzene (BEN) hydrogenation to cyclohexene (CHE) has been studied in a complex four‐phase system by using 2Ru/La2 O3 ‐ZnO as the catalyst. The catalyst is highly efficient (yield of desired cyclohexene=28 %) and stable for about five cycles. Characterizations reveal formation of La(OH)3 on the catalyst surface and formation of Zn(OH)3 − during the reaction, which play a key role in the formation of CHE. For the first time, the reaction mixture can be observed in situ, showing the emulsion of this complicated four‐phase system. The droplet size of the organic compound and the rate of hydrogenation are correlated with different stirring rates excluding mass transfer limitations. Abstract : Benzene hydrogenation : A simple 2Ru/La2 O3 ‐ZnO catalyst was tested in the selective hydrogenation of benzene. The droplet size of the organic compound in the complex four‐phase system (g/l/l/s) was determined for the first time in situ under the reaction conditions.